2016
DOI: 10.1007/s11325-016-1418-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of suicidal ideation with poor sleep quality among Ethiopian adults

Abstract: Objective To examine the extent to which poor sleep quality is associated with suicidal ideation among Ethiopian adults. Methods A cross-sectional study was conducted among 1,054 adults attending outpatient clinical facilities in Ethiopia. Standardized questionnaires were utilized to collect data on demographics, sleep quality, lifestyle, and depression status. Depression and suicidal ideation were assessed using the Patient Health Questionnaire-9 (PHQ-9), while the Pittsburgh Sleep Quality Index (PSQI) ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 27 publications
(29 reference statements)
6
22
0
Order By: Relevance
“…(1) Good Sleep Quality. After calculating the global score of sleep quality, the global score of PSQI is five and below [19,23] (2) Poor Sleep Quality. After calculating the global score of sleep quality, the global score of PSQI is above five [19,23] (3) Anxiety.…”
Section: Operational Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) Good Sleep Quality. After calculating the global score of sleep quality, the global score of PSQI is five and below [19,23] (2) Poor Sleep Quality. After calculating the global score of sleep quality, the global score of PSQI is above five [19,23] (3) Anxiety.…”
Section: Operational Definitionmentioning
confidence: 99%
“…After calculating the global score of sleep quality, the global score of PSQI is five and below [19,23] (2) Poor Sleep Quality. After calculating the global score of sleep quality, the global score of PSQI is above five [19,23] (3) Anxiety. Study participants who scored 9 and above in the Generalized Anxiety Disorder Item 7 (GAD-7) questionnaire were categorized as having anxiety [24] ( (Figure 1).…”
Section: Operational Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another large cohort study indicated that short sleepers with poor sleep quality had an increased risk of cardiovascular disease [14]. In addition, many studies [15][16][17] have indicated that poor sleep quality is a powerful predictor of suicidal ideation and depressive symptoms among the elderly. However, the underlying mechanisms between poor sleep quality and these harmful consequences are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Poor sleep quality has significant negative effects on physical and mental health, and health-related quality of life. [8][9][10] Specifically, epidemiological studies suggested that poor sleep quality is a strong risk factor strengths and limitations of this study ► This is the first study to examine the impact of sleep quality on depression symptoms among the Chinese elderly in nursing homes. ► The study provides valuable information on sleep pattern and emotional problems among the elderly in a nursing home setting.…”
Section: Introductionmentioning
confidence: 99%